Revestimentos de galactomananas e pectinas contendo óleo essencial de Lippia grata nanoencapsulado para a qualidade e controle de podridão peduncular em manga 'Palmer'. - Figueiredo, Vanda Maria de Aquino (2020)
To mitigate post-harvest deterioration and prolong the fruit's useful life, several technologies can be used, including the application of edible coatings that modify the atmosphere, promoting changes in gas exchange with the environment. The objective of this study was to determine the application potential biodegradable coatings from galactomannans and pectins in association with Lippia grata nano encapsulated essential oil in 'Palmer' mangoes produced in the sub-medium of São Francisco Valley. The experiments were carried out at the Post- Harvest Physiology Laboratory of Embrapa Semiárido, Petrolina-PE. The first experiment consisted of applying coatings based on pectins and galactomannans associated or not with L. grata nano encapsulated essential oil (EO), and the fruits were subjected to L. theobromae inoculation. The design used was completely randomized, in a factorial 5 x 7 (coating x storage time). The coatings used were: control 1 (without coating and inoculation), control 2 (without coating), pectins, pectins + EO, galactomannans, galactomannans + EO. Fruits were kept under controlled temperature (23.2 ± 2.1 ° C and 90 ± 4% RH) and evaluated for 14 days. Only the fruits coated with galactomannans remained in conditions to be evaluated until the 14th day, suggested as the most suitable galactomannan coating for use in these conditions. The second experiment featured coatings in different concentrations of galactomannans associated with the L. grata nano encapsulated OE, with all fruits inoculated with L. theobromae. The design used was completely randomized, in a factorial of 7 x 9 (coating x storage time). Three concentrations of galactomannans (0.25; 0.5; 0.75%) were tested, associated or not with EO, and the fruits kept under controlled temperature (23.8 ± 2.3 ° C and 90 ± 5% RH). The concentration of 0.5% was the one that provided the best maintenance of the mango quality, having been chosen for the third experiment, which had different forms of incorporation of the EO. The experimental design was completely randomized, in factorial 4 x 10 (coating x storage time). The coatings used were: control (without coating), galactomannan, galactomannan + nano encapsulated EO, galactomannan + EO in solution. The fruits were kept under refrigeration (11.8 ± 1.2 ° C and 90 ± 4% RH) for 15 days and then transferred to room temperature (24.5 ± 2.2 ° C and 90 ± 5% RH) for the following 10 days. A study on coatings applications under L. theobromae infection was carried out separately with all coatings used. Coatings containing EO, in both forms, provided greater maintenance of quality aspects, maintaining the green color of the skin for a longer time, providing a delay in increasing the levels of soluble solids, titratable acidity, and b- carotene content, reaching reducing sugars content higher than other coatings.